Combining ability and heterosis in maize parental lines for Turcicum leaf blight resistance - B. JAYARAMA GOWDA, SANGAM LAL; R.C. SHARMA, K.T. PANDURANGE GOWDA, H.SHEKARA SHETTY (Indian Phytopathology, 2002)
Combining ability analysis of six maize parental lines for Exser ohilum turcicum leaf blight indicated that CM-118, CM-l04 and Ade Cuba we:re good general combiners and also impart higher SCA into cross combinations. Two single crosses: exhibited maximum heterosis for disease resistance.